Examining how Nudge Theory-Based Interventions can Positively Affect Diabetes Patients on AKAP in Sikkim (Indian Journal of Public Health Research & Development, 2026)
Introduction: Diabetes mellitus, a lifestyle illness, is a major public health problem around the world, and its numbers are growing in India, and Sikkim, a northeastern state, is no exception. Sikkim, often known to have a pristine environment where people come for rejuvenation, also shares the same burden when it comes to the incidence of lifestyle diseases such as diabetes mellitus. Hence, effective management is very crucial, and it largely depends on patients' awareness, knowledge, attitude, and practices (AKAP) regarding the condition. Aim: This study aimed to examine the impact of interventions such as telephonic reminders based on nudge theory combined with ambassadors on the AKAP of diabetes patients in Sikkim. Methods: This study selected 160 diabetes patients from Sikkim via purposive sampling (80 experimental, 80 control). Both groups were asked to complete a 5-point Likert scale questionnaire to assess the Awareness, Knowledge, Attitude, and Practices (AKAP) before any intervention. The experimental group then received an intervention in the form of whatsaap messaging, telephonic calls combined with an ambassador, while the control group did not. Both the groups re-completed the AKAP questionnaire post the intervention. Data were analysed using SPSS 25, using paired t-tests for within-group comparisons and ANCOVA to study the impact between-groups. Results: Paired t-test results showed that there was no significant change in pre- and post-intervention AKAP scores for diabetes patients in the control group. Conversely, the treatment group showed a significant increase in their mean scores for awareness, knowledge, attitude, and practices related to diabetes from pre- to post-intervention. Aditionally, the ANCOVA results validated that the nudge theory-based intervention, combined with consultation, had a positive and significant impact on the awareness, knowledge, attitudes, and practices of diabetes patients. Implications: This study highlights the effectiveness of using nudge theory as an approach to improve health behaviours amongst people in Sikkim, indicating that subtle cues and consultations empower patients to make better health choices. It highlights the importance of ongoing telephonic interventions combined with ambassador or consultation for improving AKAP, resulting in enhanced self-care and reduced complications. Policymakers and healthcare providers can use these nudge based results to create health initiatives that are scalable and culturally appropriate.Conclusion: This study shows how nudge theory-based interventions, when combined with consultation, can significantly improve the awareness, knowledge, attitude, and practices of diabetes patients in Sikkim. These results indicate that such interventions can act as an effective approach to improve diabetes self-care attitude and patient’s health behaviour.
Keywords: Behavioural Intervention, Patient Education & Diabetes Management, Nudge Theory, Local Ambassador, Sikkim